Association of demographic and meteorological variables with COVID-19 occurrences and deaths - Arthur, Marcela de Mello; Freitas, Iris Tamara de; Oliveira, Victor Crespo de; Silva, Leonardo França da; Rodrigues, Sergio Augusto; Sarnighausen, Valeria Cristina; Pai, Alexander Dal; Pai, Enzo Dal (Seven Editora, 2023)
The health crisis caused by COVID-19 is considered the most severe pandemic in the last 100 years. Because it is a serious public health problem, there are many studies aimed at understanding the evolution of cases and possible associations of meteorological and demographic factors with the contamination by the virus. Given this scenario, the objective of this study is to portray, based on literature, the associations between meteorological and demographic variables with COVID-19 contamination and spread, taking into account the global panorama. Regarding demographic variables, it was found that the age group and sex of the population are associated with the spread of COVID-19. Regarding meteorological variables, scientific studies point to an association between temperature, relative humidity and air quality in advancing the spread of the COVID-19 virus. It is noteworthy that among the studies evaluated, divergences were observed in the type and level of association between demographic and meteorological variables with the spread of viruses. These results demonstrate the particularity for each region and there is a need for more specific and in-depth studies in each region.  DOI:https://doi.org/10.56238/emerrelcovid19-059